2012
DOI: 10.1080/01973533.2012.693341
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Context-Specific Norms and Group Size in Alcohol Consumption and Compliance Drinking During Natural Drinking Events

Abstract: Using experience sampling methods we examined how group size and context-specific drinking norms corresponded to alcohol consumption and compliance with drinking offers during natural social drinking events. For 30 days, 397 college students reported daily on their alcohol consumption during social events, the size of the group they were with, the average alcohol consumption of its’ members, and the number of drinks they accepted that came directly from the group they were with during these social drinking eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 54 publications
(79 reference statements)
4
27
1
Order By: Relevance
“…In naturalistic studies, the presence of others have been found to increase an individual's alcohol consumption (Eisenberg, Golberstein, & Whitlock, 2014;Thombs, Wolcott, & Farkash, 1997), an effect which appears amplified as the number of peers in the group increases (Cullum, O'Grady, Armeli, & Tennen, 2012). Comparable findings have been indicated in experimental research, whereby the presence of unfamiliar peers appears to elevate drinking amounts (Kuendig & Kuntsche, 2012).…”
Section: Social Drinkingsupporting
confidence: 54%
“…In naturalistic studies, the presence of others have been found to increase an individual's alcohol consumption (Eisenberg, Golberstein, & Whitlock, 2014;Thombs, Wolcott, & Farkash, 1997), an effect which appears amplified as the number of peers in the group increases (Cullum, O'Grady, Armeli, & Tennen, 2012). Comparable findings have been indicated in experimental research, whereby the presence of unfamiliar peers appears to elevate drinking amounts (Kuendig & Kuntsche, 2012).…”
Section: Social Drinkingsupporting
confidence: 54%
“…Indeed, research such as that by Neighbors et al (2006), Lewis et al (2011) and Thombs et al (1997) required students to consider/ estimate the number of drinks that they themselves and others consume in a number of different contexts. Similarly, Cullum et al (2012) required participants to recall the number of people they were with and the quantity of drinks they consumed in the previous night. However, this would seem problematic for a number of reasons.…”
Section: The Problems O F Retrospective Self Report Measuresmentioning
confidence: 99%
“…Social groups can vary greatly and groups may or may not remain intact over multiple nights, thereby potentially changing the likelihood of an individual experiencing a specific vulnerability on any given night. Basic indicators of group composition, such as demographics, can influence potential risk in clubs (e.g., male gender (Benson, 2002; Krienert & Vandiver, 2009; Testa, Kearns-Bodkin, & Livingston, 2009; Wells et al, 2009; Wells, Neighbors, Tremblay, & Graham, 2011), younger age (Miller et al, 2015), and larger group size (Cullum, O’Grady, Armeli, & Tennen, 2012b; McClatchley, Shorter, & Chalmers, 2014)).…”
Section: Introductionmentioning
confidence: 99%